Analisis Realisasi Anggaran Pendapatan dan Belanja Desa(APBDes) Program Pemberdayaan Masyarakat Untuk Peningkatan Kesejahteraan Masyarakat Tahun 2021-2022 (Studi Kasus Desa Nanga Sepauk) - Ningsih, Hayatun (Jurnal KIAFE, 2024)
This study analyzes the realization of the Village Revenue and Expenditure Budget for community empowerment programs and its relationship with community welfare in Nanga Sepauk Village during the 2021–2022 period. The study employs a descriptive qualitative approach. Data were collected through interviews involving village officials and residents, questionnaires distributed to at least 50 respondents, and a review of relevant documents and village records. The results show that the realization of the community empowerment program in 2021 reached 100%. In 2022, achievement in the maritime and fisheries sector reached 3%, while the agriculture and livestock sector reached 60%. The community empowerment variable obtained a total score of 72.70% and was categorized as good, although several indicators remained at the 40–50% level and therefore required further improvement. Community welfare obtained a total score of 92.29% and was categorized as very good. The empowerment budget was used for constructing fish cages, purchasing fish and livestock seedlings, providing animal feed and medicines, and supporting agricultural development. Accountability and transparency in village financial management were also implemented through monthly accountability reports and quarterly budget realization reports.